Risk Factors Correlated with Subjective Complaints of Low Back Pain in Blending Process at PT. X, 2022 - Riliyanda, Riliyanda; Novita Eka Rini, Willia; Kusmawan, David; Ena Sari, Rumita; Dermawan Sitanggang, Hendra (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Blending section workers are at risk for Low Back Pain complaints seen from every work process.  Objective: The purpose of this study was to determine the risk factors currelated with subjective complaints of Low Back Pain in blending process at PT X.  Method: The research used was observational research with a cross sectional design. The study population was blending process at PT X totaling 48 people. Result and Discussion: The results of this study indicate the prevalence of subjective complaints of Low Back Pain with moderate pain complaints felt by 76.7% of blending process. The statistical test results show that the work attitude variable (p=0.008 <0.05), the working period variable (p=0.000 <0.05), the age variable (p=0.000 <0.05), the Body Mass Index variable (p=0.815>0.05), the load weight variable (p=0.008 <0.05), the disease history variable (p=0.454>0.05) and the smoking habit variable (p=0.028 <0.05).  Conclusion: Work attitude, work period, age, weight, and smoking habits have a relationship with subjective complaints of Low Back Pain in blending process PT X.